Reflections on scaling impact: roadmap and insight on boosting Socio-Technical Innovation Bundles across Kenya - Nyamolo, Victor; Lutomia, Cosmas; Buono, Nicoletta; Ketema, Dessalegn; Gartaula, Hom; Waswa, Boaz S.; Puskur, Ranjitha; Nchanji, Eileen (CGIAR Initiative on Gender Equality, 2024)
The Gender Equality Initiative - EMPOWER has been working with partners in Kenya, Ethiopia and India to co-design, implement and scale socio-technical innovation bundles contributing to resilience, empowerment and food security. STIBs are co-designed combinations of social, technical and technological innovations to enhance climate resilience and empower men, women, youth and marginalized groups in diverse production systems. STIBs are operationalized through physical and virtual learning labs through multistakeholder engagement. HER+ Scaling Workshop held in Nairobi brought together diverse participants to reflect, deliberate on the impacts on scaling socio-technical innovation bundling (STIB) in Kenya. In addition, we developed action plan for the next year, refining and developing new activities that can increase our impact on the ground. We also had a special session with farmers to refine the bundles on the mother and baby demonstration plots. The participants comprised of Gender Equality (HER+), Diversification in East and Southern Africa (Ukama Ustawi) and Seed Equal CGIAR initiatives partners from Kenya, Ethiopia and India. We invited champion farmers from the Kenya sites, extension advisory officers and researchers from the Kenya Agricultural Livestock (KALRO), CARE International, colleagues from the Alliance of Bioversity International and CIAT, International Rice Research Institute, Green Agro Solutions PLC, Afridev Economic Consulting Limited, Sustainably Growing Africa’s Food Systems (AGRA), Organic Fields, African Plant Nutrition Institute (APNI).